2020
DOI: 10.1021/acs.jmedchem.0c00144
|View full text |Cite
|
Sign up to set email alerts
|

Re-Evaluating the Mechanism of Action of α,β-Unsaturated Carbonyl DUB Inhibitors b-AP15 and VLX1570: A Paradigmatic Example of Unspecific Protein Cross-linking with Michael Acceptor Motif-Containing Drugs

Abstract: Deubiquitinating enzymes (DUBs) are a growing target class across multiple disease states, with several inhibitors now reported. b-AP15 and VLX1570 are two structurally related USP14/UCH-37 inhibitors. Through a proteomic approach, we demonstrate that these compounds target a diverse range of proteins, resulting in the formation of higher molecular weight (MW) complexes. Activity-based proteome profiling identified CIAPIN1 as a submicromolar covalent target of VLX1570, and further analysis demonstrated that hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 35 publications
2
54
0
Order By: Relevance
“… 48 It was recently reported that total DUB activity in cell lysates is inhibited by 10 and 50 μM b-AP15. 93 The same authors reported inhibition of the activity of different recombinant DUBs using 100 μM b-AP15. This concentration is in the order of >100 times the IC 50 and difficult to interpret.…”
Section: Targets Described For Dienone Compoundsmentioning
confidence: 97%
“… 48 It was recently reported that total DUB activity in cell lysates is inhibited by 10 and 50 μM b-AP15. 93 The same authors reported inhibition of the activity of different recombinant DUBs using 100 μM b-AP15. This concentration is in the order of >100 times the IC 50 and difficult to interpret.…”
Section: Targets Described For Dienone Compoundsmentioning
confidence: 97%
“…VLX1570: VLX1570 is an analog of b-AP15 that specifically inhibits USP14 and UCHL5 with improved solubility and potency [ 179 ]. It acts via the disruption of the ubiquitin proteasome degradation pathway, leading to an increase in poly-ubiquitinated proteins, inducible forms of chaperone Hsp70 and other markers characteristic of proteotoxic stress, ER stress, and oxidative stress leading to apoptosis [ 179 , 180 ].…”
Section: Drugs Targeting Dubs In Cancermentioning
confidence: 99%
“…In 2020, Tate and co-workers re-evaluated the mechanism of action of α,β-unsaturated carbonyl compounds as DUB inhibitors [ 95 ], particularly of VLX1570 ( Figure 7 E), a compound that was put on hold in clinical trials after dose-limiting toxicity. Chemical proteomics experiments with an alkyne-tagged derivative of VLX1570 revealed CIAPIN1 as a main protein off-target.…”
Section: Specific Applications Of Bioorthogonal Reactions In Abppmentioning
confidence: 99%